An Economic ESS Design Method based on Wind System Capacity Factor for Island Power Grid - Yoon, Minhan; Jung, Seungmin (International Journal of Engineering and Technology, 2018)
Background/Objectives: Energy storage device is being considered in many fields but many system owners do not actively apply this compensation device because of the uncertainty of its criteria.Methods/Statistical analysis: In this paper, an energy capacity calculation method based on the specific capacity factor of a wind farm is introduced. The calculation method has focused on the generated surplus power, which is the difference between the generated and consumed electric power quantities.Findings: The capacity calculating method when integrating wind system has not yet been formulated steadily even though its remarkable supplementation, and previous algorithms are not considered as clear solution for various wind characteristics. In order to calculate the capacity in advance, capacity factor based pre-estimating method has been considered. Including surplus power conditions, the case studies are based on independent power-system for handling realistic environmental option and network information of an island power grid.Improvements/Applications: The surplus power was compensated during simulated conditions. In the real power-system, a minimum load could be existed for short section, and the operation would be performed more appropriately.Â Â